2016
DOI: 10.17221/16/2015-rae
|View full text |Cite
|
Sign up to set email alerts
|

The experimental research of combine harvesters

Abstract: AbstractŠpokas L., Adamčuk V., Bulgakov V., Nozdrovický L. (2016): The experimental research of combine harvesters. Res. Agr. Eng., 62: 106-112.The paper presents results of the experimental research of a middle-size combine harvester when used for harvest of winter wheat and spring barley in heavy harvest conditions. Based on the results obtained, it was possible to determine the effect of field conditions on the crop mass flow in combine harvester, grain losses, fuel consumption, and combine harvester field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 2 publications
2
29
0
1
Order By: Relevance
“…The total quantity of GSM coincides with the mass arriving to the threshing machine. According to [1][2][3][4][5][6], we determined the amount of the mass (bandwidth, q, kg/s) by dependence:…”
Section: Results Of the Study Into Degree Of Grain Separation By A Hementioning
confidence: 99%
See 1 more Smart Citation
“…The total quantity of GSM coincides with the mass arriving to the threshing machine. According to [1][2][3][4][5][6], we determined the amount of the mass (bandwidth, q, kg/s) by dependence:…”
Section: Results Of the Study Into Degree Of Grain Separation By A Hementioning
confidence: 99%
“…Therefore, we obtain discrepancy with basic indicators that are applied to seed material. Agrarians increase a rate of sowing by 20-25 % compared to sowing of conditioned seeds in response to such circumstances [3,4]. Research was conducted that established the possibility of separation of up to 35 % of grain by operative parts of a header [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Grain damage depends upon the moisture content of the threshed crop mass, upon the technological parameters of the threshing mechanism and also upon the crop mass flow [4]. The most threshing research has shown that high cylinder speed is the main factor causing corn grain damage [3,15,16].…”
Section: Grain Damagementioning
confidence: 99%
“…15), trends in grain damage remained very similar to those at the 6 kg s −1 feed rate; no significant differences in grain damage were observed between feed rates of 6 kg s −1 and 12 kg s −1 . Meanwhile, in winter wheat harvesting increase of the combine harvester feed rate caused the decrease of the grain damage [4], because thicker straw layer more absorbed rasp bar strokes.…”
Section: Grain Damagementioning
confidence: 99%
See 1 more Smart Citation